KOMUNIKASI TERAPEUTIK PERAWAT KEPADA PASIEN DI RUANG BEDAH RSUD CHASAN BOESOERIE TERNATE - Wahyuni Bailussy; Syaiful Bahry (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2018)
Research objectives include: To find out and analyze therapeutic communication that nurses treat patients in the Chasan Boesoerie Ternate Hospital Room and to find out and analyze the level of therapeutic communication knowledge for nurses in the Chasan Boesoerie General Hospital Ternate Surgery Room. The type of research that researchers use is a descriptive method, which is a method designed to gather information about real conditions in progress. Based on the results of field research that the therapeutic communication of nurses to patients during the treatment process in the operating room does not show a balanced communication attitude so that patients still feel uncomfortable over the communication that is built, as well as communication that is carried out verbally or verbally with the intention of conveying a meaningful message but not supported by nonverbal communication. Verbal communication delivered is not supported by visible expressions.